Application of Complementary Cupping Therapy for Decreased Uric Acid Levels in Gout Arthritis Patients - Sucipto, Ade; Rahayu, Sri; Qorahman MM, Wahyudi; Romaidha, Iqlila (JURNAL CITRA KEPERAWATAN, 2024)
Gout Arthritis causes high morbidity and mortality rates so serious treatment is needed. Uncontrolled gout manifests as microscopic and macroscopic accumulation of monosodium urate crystals in the form of tophi, causes complications such as inflammation, damage to joints and soft tissue which can result in nephrolithiasia (kidney stones). Prevention of complications can be done with complementary pharmacological and non-pharmacological treatments, the therapy that can be used is cupping therapy. The research design uses one group pretest and posttest design. The research population was gout arthritis patients using a non-probability sampling technique using purposive sampling technique. Data analysis was carried out using Univariate and Bivariate analysis. This study aims to analyze the effect of applying complementary cupping therapy to reduce uric acid levels in gout arthritis sufferers. Based on the research results, it shows that the significance value is 0.000, the p value <0.005, it is concluded that there is an effect of cupping on reducing uric acid levels in gout arthritis sufferers